Delphi Panel Consensus Regarding Current Clinical Practice Management Options for Demodex blepharitis - Farid M; Ayres BD; Donnenfeld E; Gaddie IB; Gupta PK; Holland E; Lindstrom R; Pflugfelder SC; Karpecki PM; Nichols KK; Starr CE; Yeu E (Clinical Ophthalmology, 2023)
Marjan Farid,1 Brandon D Ayres,2 Eric Donnenfeld,3 Ian Benjamin Gaddie,4 Preeya K Gupta,5 Edward Holland,6 Richard Lindstrom,7 Stephen C Pflugfelder,8 Paul M Karpecki,9 Kelly K Nichols,10 Christopher E Starr,11 Elizabeth Yeu12 1Gavin Herbert Eye Institute, UC-Irvine, Irvine, CA, USA; 2Wills Eye Hospital, Philadelphia, PA, USA; 3Ophthalmic Consultants of Long Island, Long Island, NY, USA; 4Gaddie Eye Centers, Louisville, KY, USA; 5Triangle Eye Consultants, Raleigh, NC and Tulane University, New Orleans, LA, USA; 6University of Cincinnati, Cincinnati, OH, USA; 7University of Minnesota, Minneapolis, MN, USA; 8Baylor College of Medicine, Houston, TX, USA; 9Kentucky Eye Institute, Lexington, KY, USA; 10University of Alabama at Birmingham, School of Optometry, Birmingham, AL, USA; 11Weill Cornell Medicine, New York, NY, USA; 12Virginia Eye Consultants, Norfolk, VA, USACorrespondence: Marjan Farid, University of California, 850 Health Sciences Road, Mail Code: 4375, Irvine, CA, 92697, USA, Tel +1 949 824-0327, Email mfarid@uci.eduPurpose: To obtain consensus on Demodex blepharitis (DB) treatment using a modified Delphi panel process.Methods: Literature search identified gaps in knowledge surrounding treatment of DB. Twelve ocular surface disease experts comprised the Demodex Expert Panel on Treatment and Eyelid Health (DEPTH). They completed a live roundtable discussion in addition to 3 surveys consisting of scaled, open-ended, true/false, and multiple-choice questions pertaining to the treatment of DB. Consensus for scaled questions using a 1 to 9 Likert scale was predefined as median scores of 7– 9 and 1– 3. For other question types, consensus was achieved when 8 of 12 panelists agreed.Results: The experts agreed that an effective therapeutic agent for treatment of DB would likely decrease the necessity of mechanical intervention, such as lid scrubs or blepharoexfoliation (Median = 8.5; Range 2– 9). When treating DB, panelists believed that collarettes serve as a surrogate for mites, and that eliminating or reducing collarettes should be the main clinical goal of treatment (Median = 8; Range 7– 9). The panelists would treat patients with at least 10 collarettes, regardless of other signs or symptoms and agreed that DB can be cured, but there is always the possibility for a reinfestation (n = 12). There was also consensus that collarettes, and therefore mites, are the primary treatment target and the way by which clinicians can monitor patient response to therapy (Median = 8; Range 7– 9).Conclusion: Expert panelists achieved consensus on key facets of DB treatment. Specifically, there was consensus that collarettes are pathognomonic for DB, that DB patients with > 10 collarettes should be treated even in the absence of symptoms, and that treatment efficacy can be tracked by collarette resolution. By increasing awareness about DB, understanding the goals of and monitoring treatment efficacy, patients will receive better care and, ultimately, better clinical outcomes.Keywords: collarettes, cylindrical dandruff, ocular surface disease, eyelid disease